Haemodynamics and post-exercise recovery response in COPD-PH and ILD-PH: An appraisal - Sayoni Sengupta; Parthasarathi Bhattacharyya; Aniruddha De; Sayanti Karmakar; Wrick Chakraborty; Dipanjan Saha (Lung India)
Background: Chronic lung disease (CLD) from either airway obstruction or parenchymal affections can lead to secondary pulmonary hypertension. It may be interesting to compare the two types of CLD-PH. Methods: Subjects of CLD were first evaluated for the primary category of disease with chest X-ray, HRCT chest, spirometry, and DLCO (diffusion capacity) and then for the presence of PH through exercise of the institutional clinic-radio-echocardiographic algorithm. Those qualifying as either unmixed restrictive (ILD) or COPD (chronic obstructive airway disease) with PH underwent two-chair test for assessment of post-exercise recovery response. The two groups were compared on available parameters. Results: The patients with COPD-PH were significantly older with similar FVC and DLCO compared to ILD-PH. In two-chair test, the maximum pulse rate and the desat-max were significantly worse (108.68 ± 1 5.46 vs 101.33 ± 12.62, P = 0.002, and − 5.68 ± 4.78 vs − 3.71 ± 2.73, P = 0.006) for the ILD-PH patients. The ILD-PH sufferers also demonstrated a lower TAPSE (21.16 ± 3.11 vs 22.59 ± 2.71; P-0.001) and a higher calculated mean pulmonary artery pressure (32.00 ± 7.54 vs 30.64 ± 4.22 vs, P = 0.05) compared to the subjects with COPD-PH. The other right ventricular systolic functional parameters [systolic excursion velocity (S-prime), right ventricular free wall global longitudinal strain, systolic pulmonary arterial pressure, tricuspid regurgitation jet velocity] supported the trend. Conclusion: The ILD-PH patients show relatively higher PH with lower right ventricular systolic function than COPD-PH.